Hidrogel Superabsorben Berbasis Natrium Alginat-Bentonit sebagai Pelapis Pupuk Lepas Lambat - Sintia Lestari; Lela Mukmilah Yuningsih; Salih Muharam (Jurnal Riset Kimia, 2022)
The application of slow-release fertilizer in agriculture is currently very necessary because of its performance that can control the release of fertilizer. However, the case of excessive use of urea on agricultural land has the potential to cause water pollution because the process of nitrification produces nitrite ions that are toxic and eutrophication of water and prevent harmful N2O gas emissions. This research has been done making urea slow-release fertilizer in the form of superabsorbent hydrogel with crosslink method and bentonite coating technique by sodium alginate. The hydrogels formed characterized its structure and morphology with FTIR and SEM-EDS, as well as swelling tests to see its ability to store water. Furthermore, to test the performance of hydrogel as a slow-release fertilizer is carried out urea release test at various pH and times. The results showed that urea fertilizer has filled the structure and surface of hydrogel with a swelling ratio of 2.894,30% (BAC1) and 3.428,52% (BAC2). The addition of CaCl2 crosslinking agent provides increased gelation power, swelling, and adsorption capacity against urea in addition to the urea release process is not affected by pH.